Evaluation of urology trainee preferences in didactic education: a choice-based conjoint analysis - Li, Yi; Spradling, Kyle; Allen, Isabel Elaine; Conti, Simon; Hampson, Lindsay A. (Frontiers in Medicine, 2023)
Purpose Didactic lectures are a commonly used educational tool during urology residency training. Recently, there has been a rapid introduction of online, collaborative didactics as a new model for resident teaching. The aim of this study is to determine which attributes of didactics education are most preferred by contemporary urology trainees. Methods Urology trainees were invited to complete an online choice-based exercise assessing combinations of four attributes associated with didactics education: mode of communication, learning style, presenter credentials, and curriculum design. The survey was distributed via social media platforms and the Urology Collaborative Online Video Didactics (COViD) website. A choice-based conjoint analysis was used to identify how the trainees valued different combinations of didactic education. Results Seventy-three trainees completed the conjoint analysis exercise. Mode of communication was rated as significantly more important than curriculum design (relative importance 28.6% vs. 19.9%). Overall, the majority preferred online/virtual presentations to in-person presentations. Respondents preferred national experts to faculty members from their local institutions, and preferred cased based lectures to didactics style lectures. A nationally standardized curriculum was also preferred over curriculum designed by local institutions. Finally, when segmented by level of training, there was increased preference for overall favored options as PGY year increased. Conclusion This conjoint analysis shows clear preference by trainees for online, recorded didactics, nationally standardized with national experts, and preferably in a case-based format. Academic societies in urology and program directors should consider utilizing the shared experience of previously created collaborative online lectures in developing future didactic curriculum that can meet the needs of current trainees.